Conformal ultrathin on-skin electrodes with reusability, breathability and invisibility - Yu, Shujin (Nanyang Technological University, 2023)
On-skin electrodes, as important basic units of wearable devices, is becoming an emerging research area for healthcare application. Improvement on different properties of on-skin electrodes is widely investigated, in particular to enhance the stretchability and conductivity, while user-interface related properties also play a vital function in research and development of device for electrophysiological signals monitoring. However, gap exists in electrode materials with properties including reusability for repeated adhesion, breathability for sweat evaporation, and invisibility for aesthetic purposes, at the same time. Herein, a bacterial cellulose based ultrathin film with thickness of about 5 μm is developed as substrate material for conformal on-skin electrodes which possess reusability, breathability, and invisibility simultaneously. With glycerol plasticization, the Young’s modulus of the cellulose ultrathin film can be modified and reduced from 1 GPa of pure cellulose ultrathin film to around 100 MPa, which is comparable to the modulus of human stratum corneum. The glycerol-plasticized cellulose film is tested to have repeated usability, high water vapor transmission rate and superior invisibility on skin. With combination of poly(3,4- ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS), the cellulose/PEDOT: PSS ultrathin film can achieve a conductivity of around 100 S/m after post-treatment, which is increased over 5 times higher compared with direct spin coating of PEDOT: PSS aqueous solution. The proposed on-skin electrodes display a relatively low impedance and high signal-to-noise ratio comparable to commercial Ag/AgCl electrodes in electromyography (EMG) signal monitoring. The user-friendly interface and high signal capture performance provide great potential for it to be applied in future commercialized on-skin electronics products.